Comparative Study of the Psychological Needs between Kindergarten Children with Developmental Learning Disabilities and Normal - Nawaf. M. Aldhafeeri (Sultan Qaboos University, 2015)
The study aimed to identify the psychological needs (for competence, autonomy, and affiliation) with kindergarten children in Kuwait. A sample of 117 children from kindergarten (57 with developmental learning disabilities, and 60 of normal children) was selected. Two instruments were used: early detection tool and psychological needs scale. The results showed that there were significant differences (p. < 0.01) between the developmental learning disabilities and the normal children in all needs. Also, there were significant differences (p. < 0.05) between males and females in competence and autonomy needs. There were no significant differences between males and females in the affiliation need. There were significant Interaction effect between gender and the group in the autonomy need indicating that differences due to gender are not constant.